(untitled) (Conferencea, 2022)
Foreign language study is all about learning how to truly communicate and connect with others—an incredibly important life skill that can only be cultivated by interacting with people. When you master a foreign language, you can exercise your new superhuman power of being able to understand what someone is saying, recall the proper vocab and grammar, put that vocab and grammar into the proper context, and reply back—all on the spot and in a timely manner. You’ve connected. And that is what it’s all about.